2017
DOI: 10.1007/s12402-017-0221-1
|View full text |Cite
|
Sign up to set email alerts
|

The risk of misdiagnosing posture weakness as hyperactivity in ADHD: a case study

Abstract: Difficulties in sustaining posture can present with features associated with hyperactive behaviour listed in DSM-5 and ICD-10 classifications for ADHD. Information from a system measuring motor activity during a neurocognitive test (QbTest), occupational therapist reports and Conners rating scales are compared between cases with and without posture problems. Weakness in sustaining posture results in elevated activity measures during infrared motion analysis. Strong posture on the other hand appears to mitigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…They included two studies in which the CPT was combined with other measures such as information provided by a teacher or parents and suggested that rating scales and TOVA are measuring distinct but important aspects of ADHD, and the addition of TOVA makes a valuable contribution to assessment of ADHD. Also, according to Vogt (2017) , questionnaires are based on behavioral presentations and the correlation with neurocognitive tests is known to be low to moderate. In the future it would be interesting to compare the information provided by parents and teachers with performance in traditional and virtual CPTs.…”
Section: Discussionmentioning
confidence: 99%
“…They included two studies in which the CPT was combined with other measures such as information provided by a teacher or parents and suggested that rating scales and TOVA are measuring distinct but important aspects of ADHD, and the addition of TOVA makes a valuable contribution to assessment of ADHD. Also, according to Vogt (2017) , questionnaires are based on behavioral presentations and the correlation with neurocognitive tests is known to be low to moderate. In the future it would be interesting to compare the information provided by parents and teachers with performance in traditional and virtual CPTs.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is quantitatively a difference between the two groups, the high variance of activity in both groups suggests additional heterogeneity, pointing out to a more complex interplay with other factors that can influence activity other than those related to executive functions as described above, for example motor control (e.g. overflow movements) and motor timing difficulties, mechanical posture weakness, sensory modulation disorder and subcortical impairment [5,[25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The QbTest can help identify mechanical posture weakness as shown in a case study by Vogt. 23 The tracking of movement on the visual display from the report produces distinct configurations (►Fig. 3) as a result of slouching and stretching (condensed double clumping markings; increases in vertical body movement especially in the latter half of the test) that are easily identified.…”
Section: Activitymentioning
confidence: 99%